PRINCIPLE OF TEACHING DRAFT GEOMETRY AND COMPUTER GRAPHICS - Mamurova Dilfuza Islamovna; Muhammadova Gulhumor (Scholar Express Journal, 2021)
The pedagogical skill of the teacher is to select the necessary content, to apply the best teaching methods and means in accordance with the program and the set educational tasks in descriptive geometry and computer graphics. Pedagogical skill of the teacher is to select the right content, to apply optimal methods and means of teaching in accordance with the program and delivered educational tasks acertinaedje geometry and computer graphics.
Keywords: pedagogical technology; methods; computer graphic; anthology